FORMULATION OPTIMISATION OF ROLLED PANCAKE WITH RED DRAGON FRUIT’S SKIN USING RESPONSE SURFACE METHODOLOGY - Faridah, Anni Faridah (Universitas Dr Soetomo, 2019)
Kue Dadar (lit. pancake) is a green-coloured Indonesian cake, but in recent years it saw the colouring of the pancake is mainly using synthetic colouring. This type of colouring can be substituted with natural colourings such as Betalain, gathered from the skin of the red dragon fruit. The skin is also beneficial for human because it also contains fibre, pectin, and other nutritious contents. This research aims to obtain the formulation of red dragon skin pancake, using the factors of red dragon skin?s amount (X1), egg?s amount (X2), and thick coconut milk?s amount (X3). This research will be conducted through experiments, utilising Response Surface Methodology (RSM) and Central Composite Design (CCD). Data analysis will be assisted by Software Design Expert ver. 7.1. The results of this pancake formulation?s optimisation are 89.73 grams of red dragon fruit skin, 39.99 grams of egg, 167.78 ml of thick coconut milk and have a quadratic characteristic. Analysis results of R2 and Adjusted R2 by colour and texture response are 0.8720; 0.9500 and 0.9327; 0.9049 respectively. Response values on its optimal condition are 5.47 for colour and 5.62 for texture. Other quality values are 5.00 for shape (good shape), 5.23 for aroma (good smell), and 4.90 (sweet flavour).